2017
DOI: 10.1007/s00231-017-2040-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and performance of heat pipes with long evaporator sections

Abstract: thermal model using a resistance network was created. The model compares well with the measurement data, especially for higher input powers. Finally, the thermal model is used for the design of a 1 kW planar system-level electronics cooling infrastructure featuring six 1 m heat pipes in parallel having a long (~75%) evaporator section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A geyser boiling effect was observed and there was an operation limit for heat inputs larger than 160 W for all FRs. During operation, the TPCT could encounter various limitations such as the viscous limit, sonic limit, entrainment limit, boiling limit, and capillary limit [9]. As can be seen in Figure 21, boiling limit is encountered in this case.…”
Section: Effect Of Geyser Boiling Influences and Boiling Limit On Opementioning
confidence: 93%
See 1 more Smart Citation
“…A geyser boiling effect was observed and there was an operation limit for heat inputs larger than 160 W for all FRs. During operation, the TPCT could encounter various limitations such as the viscous limit, sonic limit, entrainment limit, boiling limit, and capillary limit [9]. As can be seen in Figure 21, boiling limit is encountered in this case.…”
Section: Effect Of Geyser Boiling Influences and Boiling Limit On Opementioning
confidence: 93%
“…Experiments have been performed for distilled water as a working fluid with an FR equal to 0.75 and for various power inputs from 71 W to 960 W. It has been confirmed that a new type of condenser section in a TPCT could enhance the performance from 10% to 17% compared to the unmodified version of a thermosyphon. W. Wits and G. Riele [9] have worked on a cooling strategy for advanced electronic applications using heat pipe technology. The authors' idea was based on using an array of relatively long heat pipes, whereby heat was disposed to a long section of the pipes.…”
Section: Introductionmentioning
confidence: 99%
“…The phase-change heat transfer performance here, to a large extend, determine the thermosyphon's overall heat transfer performance. In contrast, heat pipes use a wick structure to 978-1-6654-1896-6/21/$31.00 ©2021 IEEE return the working fluid by capillary force [2]. Although wick structures help to return the working fluid and improve evaporation and boiling heat transfer, they generally increase the system's thermal resistance [3].…”
Section: A Background and Literature Reviewmentioning
confidence: 99%
“…The condenser capacity will be reduced due to overcharging, whilst the artery may be dried out due to undercharging. Providing an extra fluid reservoir that will absorb surplus fluid while also being non-required by the primary wick structure [11], [12] is the research topic at hand. Calculation of operating limits and parameters limit, entrainment limit, sonic limit, boiling limit and viscous.…”
mentioning
confidence: 99%